Role as A Consultant For Islamic Extension in Empowering The Taklim Assembly in Talawi District, Batubata Regency, North Sumatra Province - Rudi, Muhammad; OK, Azizah Hanum; Arsyad, Junaidi (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
This article discusses Islamic religious extension workers who act as consultants in empowering the Taklim Assembly in Talawi District, Batubara Regency. Data collection was in the form of observation techniques, interviews and documentation studies. The data obtained in the field is then collaborated with data from the literature study. The technique exhibits the characteristics of qualitative research. The research results obtained were that the Islamic Religious Counselors in the Talawi District, Batubara Regency had and carried out their duties according to their functions. The focus of his duties is in accordance with the provisions set by the Head of the Batubara Regency Office of Religious Affairs. Associated with the taklim assembly, the Islamic Religion Counselor acts as a provider of opinions, directions, advice and solutions regarding the achievement of the functions and objectives of the formation of the Taklim Assembly. Efforts made are: giving advice to always make the Qur'an a way of life, providing solutions for efforts to find leaders from members of the Taklim Assembly, providing advice related to strengthening human relations with Allah and others, providing opinions, instructions, advice and solutions in religious and religious discussion activities, providing directions and solutions to improve the family economy, providing directions related to the development of Islamic arts and culture; and giving advice and directions to love religion, nation and state